Reverse effect of mammalian hypocalcemic cortisol in fish: cortisol stimulates Ca2+ uptake via glucocorticoid receptor-mediated vitamin D3 metabolism. - Chia-Hao Lin; I-Lun Tsai; Che-Hsien Su; Deng-Yu Tseng; Pung-Pung Hwang (PLoS ONE)
Cortisol was reported to downregulate body-fluid Ca(2+) levels in mammals but was proposed to show hypercalcemic effects in teleostean fish. Fish, unlike terrestrial vertebrates, obtain Ca(2+) from the environment mainly via the gills and skin rather than by dietary means, and have to regulate the Ca(2+) uptake functions to cope with fluctuating Ca(2+) levels in aquatic environments. Cortisol was previously found to regulate Ca(2+) uptake in fish; however, the molecular mechanism behind this is largely unclear. Zebrafish were used as a model to explore this issue. Acclimation to low-Ca(2+) fresh water stimulated Ca(2+) influx and expression of epithelial calcium channel (ecac), 11β-hydroxylase and the glucocorticoid receptor (gr). Exogenous cortisol increased Ca(2+) influx and the expressions of ecac and hydroxysteroid 11-beta dehydrogenase 2 (hsd11b2), but downregulated 11β-hydroxylase and the gr with no effects on other Ca(2+) transporters or the mineralocorticoid receptor (mr). Morpholino knockdown of the GR, but not the MR, was found to impair zebrafish Ca(2+) uptake function by inhibiting the ecac expression. To further explore the regulatory mechanism of cortisol in Ca(2+) uptake, the involvement of vitamin D(3) was analyzed. Cortisol stimulated expressions of vitamin D-25hydroxylase (cyp27a1), cyp27a1 like (cyp27a1l), 1α-OHase (cyp27b1) at 3 dpf through GR, the first time to demonstrate the relationship between cortisol and vitamin D(3) in fish. In conclusion, cortisol stimulates ecac expression to enhance Ca(2+) uptake functions, and this control pathway is suggested to be mediated by the GR. Lastly, cortisol also could mediate vitamin D(3) signaling to stimulate Ca(2+) uptake in zebrafish.